Assessment on Knowledge and Perception Regarding Health Risks of Pesticide Usage Among Farmers - Priyanka Anbazhagan (International Journal of Public Health Science (IJPHS), 2022)
Pesticides are essential substances that is economical, labor saving and efficient tool among the farmers with significant importance in increasing food production and pest management in developing countries. Although, the serious concern about the health risk of pesticide toxicity should be investigated. The aim of the study is to assess the knowledge & perception of health risks of pesticide usage among farmers. This online-based descriptive cross-sectional study was conducted among farmers in Namakkal district, Tamil Nadu. A validated questionnaire was prepared in two languages for convenience, assessing the sociodemographic and analyzing the level of awareness, perception of pesticide usage among farmers. About 412 farmers participated, in which 98.5% use pesticides and 64.5% were males. Among them, 72.4% of farmers do not use personal protective equipment (PPE) while applying pesticides, 75.5% dispose and 24.5% of farmers re-use the empty pesticide bottle. Also, 68 % are not aware of the harmful effects of pesticides even though 94.5% experienced health related problems while using them. Therefore, 95.4% of farmers think it is necessary to create awareness about safe handling practice and health risks regarding the usage of pesticides. Our study reveals that farmers do not have adequate knowledge about safe pesticide handling and are not aware of pesticide toxicity levels along with the risk associated with the degree of toxicity which is essential for implementing strategies regarding pesticide safety education and training.